Association of Body Mass Index and Other Factors with Histamine Skin Reactivity in Adults with Allergic Nasal Symptoms. Issue 6 (November 2015) - Park, Do Yang; Kim, Yoo Suk; Kim, Jeong Hong; Kang, Ju Wan
Background: The skin-prick test is the most commonly used method to diagnose allergy. In addition, histamine skin reactivity is used as a positive control for the skin-prick test. However, there is individual variation in histamine skin reactivity. The factors that influence individual variation in histamine skin reactivity remain unknown. Objectives: We aimed to investigate the factors associated with histamine skin reaction. Methods: Ninety-seven subjects who underwent a skin-prick test to diagnose allergic rhinitis were enrolled in this study. The skin-prick test was performed with six common allergens. The wheal size of the histamine skin reaction was analyzed; other variables included age, sex, body mass index (BMI), atopy, smoking history, and the testing season. Results: The wheal size in the histamine skin test was significantly associated with age and BMI. The association between histamine skin reactivity and BMI was also present in multivariate analysis, adjusted for age, sex, atopy, smoking history, and season. Conclusion: Histamine skin reactivity increased with BMI (degree of obesity). This association should be considered for better interpretation of the skin-prick test. Further studies regarding the mechanism for this association are needed.